2009
DOI: 10.1063/1.3272536
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of ultrafast nonradiative transitions in nitro-polycyclic aromatic hydrocarbons: Excited-state dynamics in 1-nitronaphthalene

Abstract: The electronic energy relaxation of 1-nitronaphthalene was studied in nonpolar, aprotic, and protic solvents in the time window from femtoseconds to microseconds. Excitation at 340 or 360 nm populates the Franck-Condon S(1)(pipi( *)) state, which is proposed to bifurcate into two essentially barrierless nonradiative decay channels with sub-200 fs lifetimes. The first main decay channel connects the S(1) state with a receiver T(n) state that has considerable npi( *) character. The receiver T(n) state undergoes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

31
241
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 124 publications
(273 citation statements)
references
References 75 publications
31
241
1
Order By: Relevance
“…31 Excitation energies converged to 0.07 eV or better in all cases. It has been shown that the PBE0 functional provides accurate excited-state energies (within ∼0.2 eV), 43−46 singlet−triplet energy gaps, 46,47 and excited-state ordering, 43,46,48 particularly when solvent effects using the PCM solvation model are included in the calculations.…”
Section: Experimental and Computational Methodsmentioning
confidence: 95%
“…31 Excitation energies converged to 0.07 eV or better in all cases. It has been shown that the PBE0 functional provides accurate excited-state energies (within ∼0.2 eV), 43−46 singlet−triplet energy gaps, 46,47 and excited-state ordering, 43,46,48 particularly when solvent effects using the PCM solvation model are included in the calculations.…”
Section: Experimental and Computational Methodsmentioning
confidence: 95%
“…In contrast, ISC was expected to be considerably slower when the SOCs are very small, as is the case in organic molecules composed solely of light atoms of the first period. For certain classes of organic molecules, such as nitro polycyclic aromatic hydrocarbons (NPAHs)3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14 and the closely related nitrobenzene derivatives,15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25 ISC has been measured to occur in an ultrafast sub‐picosecond timescale, challenging this paradigm.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of molecules where ISC is important range from aldehydes [37] and small aromatic compounds like benzene, [38] naphthalene, anthracene, and their carbonylic derivatives [39][40][41][42][43][44][45][46][47][48][49][50][51] to nitrocompounds. [43,[52][53][54][55][56][57][58][59][60][61] Furthermore, ISC has been reported for thio-substituted, [62][63][64][65][66][67][68] aza-substituted, [69] bromo-substituted, [70] and canonical nucleobases. [71][72][73] From a theoretical point of view, ISC can be explained by the interaction of states of different multiplicity by spin-orbit coupling (SOC), which is a relativistic effect.…”
Section: Introductionmentioning
confidence: 99%